Meta-analysis of the Sociological Factors Influencing Singleness among Iranian Young Adults (A Case Study of Individuals Aged 25 to 40 in Tehran) - Mohammad Nemati; Taghi Azad Armaki; Alieh Shekarbeagi (Iranian Evolutionary Educational Psychology Journal, 2023)
Objective: Evolutionary psychology posits that humans tend to naturally choose mates based on traits that signal reproductive fitness. Nevertheless, contemporary Iranian society is witnessing a trend towards delayed marriage and a growing individuals' inclination towards singleness. This research aimed to explore this phenomenon by conducting a structural equation model focusing on singleness in Iran, particularly seeking to comprehensively understand the sociological factors influencing the decision of young adults aged 25 to 40 in Tehran to remain single. Methods: To explore this subject comprehensively, a mixed research approach, encompassing both qualitative and quantitative methods, was employed. In the qualitative phase, an extensive review of published articles in the relevant field was conducted. Additionally, a subset of the sample population, consisting of 384 individuals, was analyzed using Cochran's sampling method to validate the qualitative findings. The research outcomes, derived from both the quantitative and qualitative dimensions, illuminated a multitude of factors influencing the inclination of Iranian youth toward singleness. Results: These findings, obtained through thorough analysis, underscored the significant impact of various factors, including social, economic, political, and cultural influences, as well as the personal characteristics of unmarried individuals and their level of education. Conclusions: These factors collectively contribute to the prevalence of singleness.